Adenine base editing to treat progeria syndrome and extend the lifespan - Musunuru, Kiran (J Cardiovasc Aging, 2021)
Hutchinson-Gilford progeria syndrome (HGPS) is an exceedingly rare and hitherto incurable and fatal disease marked by accelerated aging simultaneously affecting a number of organs. Most cases of HGPS are caused by a single copy of a specific single-nucleotide mutation, c.C1824T, in the LMNA (lamin A) gene. Different mutations in LMNA are responsible for a variety of disorders affecting a variety of organs, including dilated cardiomyopathy, familial partial lipodystrophy, Emery-Dreifuss muscular dystrophy, limb girdle muscular dystrophy, Charcot-Marie-Tooth disease, and restrictive dermopathy. The unique pathophysiology of HGPS arises from the distinctive nature of the c.C1824T mutation; despite being a synonymous mutation that does not directly change an amino acid in the lamin A protein, it nonetheless exerts a profound effect on the protein by creating a cryptic splice site that causes incorrect splicing of the LMNA mRNA transcript, resulting in production of a truncated form of lamin A termed progerin, which is constitutively farnesylated. The farnesylated protein inappropriately accumulates in cells and causes dysregulation of the nuclear lamina - a structure in which the normal lamin A protein is a key component - that results in cellular dysfunction, senescence, and death. Vascular smooth muscle cells (VSMCs) represent one of the cell types particularly affected by progerin, and cardiovascular complications are the typical cause of death of HGPS patients in their youth.